2018
DOI: 10.1177/2332858418758299
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Category Functioning of the ECERS-R Across Eight Data Sets

Abstract: Major policy efforts aim to make preschool universally available and improve the quality of child care settings, with a goal of preparing all children for school (Child Trends, 2015; Pew Charitable Trusts, 2014; U.S. Department of Education, 2013). Importantly for our study, policies often dictate that observational measures are incorporated in an attempt to ensure high classroom quality. Often, raw scores (e.g., averaging across all items) from these measures are compared to cut scores, contributing to conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Rather low ECERS-R total scores were also obtained in many countries (for example, in Netherlands (De Kruif et al, 2009), Bahrein (Hadeed, 2013), Brazil (Mariano et al, 2018), Columbia (Betancur et al, 2021) etc. ), that lead researchers to propose changes in the stop-coding system of ECERS-R indicators assessment that we support (Fujimoto et al, 2018).…”
Section: Discussionmentioning
confidence: 75%
“…Rather low ECERS-R total scores were also obtained in many countries (for example, in Netherlands (De Kruif et al, 2009), Bahrein (Hadeed, 2013), Brazil (Mariano et al, 2018), Columbia (Betancur et al, 2021) etc. ), that lead researchers to propose changes in the stop-coding system of ECERS-R indicators assessment that we support (Fujimoto et al, 2018).…”
Section: Discussionmentioning
confidence: 75%
“…It was also suggested that there is redundancy between the 43 items and that the seven subgroups provided similar measures (Fujimoto, Gordon, & Hofer, 2018;Perlman et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This is also the case with other IRT models, such as the graded response model and the partial credit model. The literature on reversals is sparse, and while some researchers (eg, the work of Adams et al) argue that reversals do no necessarily reflect model misfit, others (eg, Fujimoto et al) have argued that reversals may be problematic to the validity of a scale Update sufficient statistics: 𝛍jkfalse(tfalse)=𝛍jkfalse(t1false)+γt{}truex¯jk𝛍jkfalse(t1false) -1ptboldΣfalse(tfalse)=boldΣfalse(t1false)+γt{}S2Σ(t1), where γ t is the current value of the Robbins‐Monro gain coefficient.…”
Section: Saem Algorithm For Exploratory Irt Factor Analysismentioning
confidence: 99%